Analyzing Moral Deliberation During Gameplay: Moral Foundations Theory as an Analytic Resource. Issue 7 (November 2019) - Fennewald, Thomas; Phelps, David
This article explores the role of interplayer moral conversation in multiplayer games with three subquestions: how to design and use games for morality research, how advances in moral theory can inform game-based research into morals, and how game-based research can inform moral theory. A long tradition has investigated morals using games such as Ultimatum and Dictator ; however, this research often omits interplayer moral dialogue. Further, when moral foundations theory is accounted for, analysis of these games seems to investigate a narrow range of moral reasoning. In this methodological critique, we draw upon data from gameplay of a simulation of climate change debate and find a wide range of moral foundations through analysis of dialogue. Our analysis suggests that in-game player dialogue is a source of rich moral deliberation and potential for using simulation games as grounds for discovering new moral foundations.